China Benteng: A Refutation of Ethnic Chinese Exclusivity in Indonesia : (A Critical Discourse Analysis of YouTube Content 'The Story') - Fallah Ilham, Naufal; Kartika, Tina Kartika; Corry Wardhani, Andy; Juansya, Andri; Amri, Andi (COMMICAST, 2025)
This study investigates the representation of the Chinese ethnic minority, particularly the Benteng Chinese community in Tangerang, as portrayed in the documentary film China Benteng: Dari Waktu ke Waktu, aired on the YouTube channel The Story. Employing Teun A. van Dijk’s Critical Discourse Analysis framework, the research analyzes three interrelated dimensions: text structure, social cognition, and social context. The findings reveal that the documentary challenges entrenched stereotypes about the Chinese-Indonesian community, particularly assumptions of economic uniformity and cultural isolation, by emphasizing socioeconomic diversity and cultural assimilation. At the macrostructural level, the film highlights the simplicity of the Benteng Chinese lifestyle and their long-standing integration with local communities. Through its superstructure and micro-level elements, the documentary employs visual and verbal narratives to underscore the active participation of the Benteng Chinese in broader Indonesian social life. The social context dimension illustrates an effort to counter dominant narratives and empower marginalized voices. Meanwhile, the producer’s social cognition appears deliberately neutral, allowing the community to articulate their own narratives authentically. This study contributes to the growing body of research on media representation and ethnic discourse by providing a nuanced analysis of how documentary filmmaking can act as a counter-discursive tool. It enriches the understanding of ethnic minority portrayals in Indonesian media, and underscores the documentary genre’s potential to facilitate intercultural dialogue, challenge dominant ideologies, and expand the representational space for historically marginalized groups.